Imprint of Mesospheric Quasi 2-Day Wave in the Ground Geomagnetic Field Variations at Low Latitudes - Jadhav, Ashish; Gurubaran, S.; Ghodpage, R.; Patil, P. T.; Batista, Paulo P. (My University, 2023)
The strong quasi 2-day wave (Q2DW) event that occurred during January 2015 was studied by employing medium frequency and meteor radar observations of winds from three different locations at low latitudes with considerable longitudinal separation. The large-amplitude wave activity that occurred in mid-January is the focus of this study. Using the advantage offered by the longitudinal separation among the stations, the zonal structure of the Q2DW has been examined. The presence of a dominant westward propagating zonal wavenumber 3 (W3) mode was revealed in the analysis. The availability of geomagnetic field data from a number of stations at low latitudes enabled us to observe the wave event at ionospheric dynamo region heights. The phase-longitude cross-section of the quasi 2-day oscillation in the Y component of the geomagnetic field reiterates the presence of the dominant W3 mode observed at lower altitudes. Similar zonal characteristics and periods of the wave signatures found at mesospheric altitudes and in the manifestation of quiet-time ionospheric currents in geomagnetic field are in conformity with the notion of the wave coupling of the atmosphere-ionosphere system. Plain Language Summary This study examines the strong quasi 2-day wave event that occurred during January 2015 at low latitudes using medium frequency and meteor radar observations. The analysis reveals the presence of a dominant westward propagating zonal wavenumber 3 mode. Geomagnetic field data from multiple stations at low latitudes show similar zonal characteristics and periods of the wave signatures, which suggests wave coupling of the atmosphere-ionosphere system.
Keywords: Geomagnetic field; Quasi 2-day wave; Meteor radar observations; Atmosphere-ionosphere system